Application of a conventional paravertebral block on the thorax with a novel intrathoracic approach during the intraoperative period: Two case reports: Paravertebral block with an intrathoracic approach - Mendes , Ergun; Semerkant , Tolga; Cok , Oya Yalcin (Journal of Surgery and Medicine, 2023)
Pain management significantly reduces mortality by aiding in the effective elimination of secretions after thoracic surgery. We present two cases requiring emergency surgical intervention due to major trauma. Both patients were provided pain control with an intrathoracic approach of the paravertebral block performed by a sterile-clothed anesthetist with a single-shot 20 ml injection of 0.25% bupivacaine from the inner surface to the superior costo-transverse ligament (SCTL). After extubation, the measured VAS score was no higher than 3–4, and the patients could breathe and cough comfortably. The intrathoracic approach may be an effective method to implement for postoperative acute pain.